Gender, generations and domestic environment: work, house and family - Lago, Mara Coelho de Souza; Souza, Carolina Duarte de; Kaszubowski, Erikson; Soares, Marina Silveira (Paidéia (Ribeirão Preto), 2009)
With the conceptual changes brought by the "difference feminism", feminist studies re-evaluated the poles of positive and negative valorization of women's and men's roles, focusing on feminine characteristics, attributions and functions. As a consequence of these studies and practices they guide, it was possible to value the domestic environment and tasks that both men and women perform in this environment. This study aimed to develop a gender study about the house, analyzing the relationship of the individuals with their family life spaces, trying to value the domestic work and to understand its subjective meaning. This qualitative study with ethnographic approach was carried out through taped and video recorded free interviews aiming to capture the testimonials and images of the participants in their homes during tasks. A total of 12 women and 5 men from different generations and professions were interviewed in Antônio Carlos in the metropolitan region of Florianópolis, SC, Brazil.